Evaluating reasons for biased sex ratios in Crustacea. Issue 3 (3rd July 2019) - Ewers-Saucedo, Christine
ABSTRACT: While equal ratios of males and females are normal, crustacean sex ratios are frequently biased. Here I review potential reasons for sex ratio biases in animals, and evaluate how likely they apply to crustaceans. I introduce crustacean examples and highlight promising crustacean taxa for future studies where examples are lacking. I conclude that ecological differences between the sexes appear to be the dominant reason for sex ratio bias in crustaceans. Major life history patterns limit the importance of evolutionary drivers to sedentary taxa with limited dispersal. Still largely unresolved is the question whether females can bias their offspring sex ratio, and given the diversity of sex determining systems, answers will vary from case to case. Abbreviations: LMC: local mate competition; LSC: local sperm competition.